Proposta de adaptação de método de análise do trabalho em uma instituição de ensino superior do Mato Grosso - Bulhões, Gevanil Lene Arruda (Universidade Federal de São Carlos, 2025)
The increasing complexity of production processes and the intensification of labor demands make occupational risks less visible and more difficult to manage, reinforcing the need for instruments that guide the organization and monitoring of working conditions. In this context, this study aimed to adapt the MPEC method for analyzing and transforming work in a public university, based on ergonomic principles. This is an exploratory and qualitative research, supported by two analytical dimensions: (i) understanding the institutional reality through bibliographic review and documentary research; and (ii) the perception of workers, obtained through structured interviews analyzed according to the content analysis technique. The results showed that, although the institution has defined guidelines and goals, a large part of the actions remains concentrated in the prospective phase, with limited, fragmented, and poorly monitored execution. The techniques that comprise the MPEC demonstrated high acceptance, with averages ranging from 8.3 to 9.5, indicating recognition of their practical relevance. However, significant limitations emerged during its implementation, including a scarcity of material and financial resources, a lack of prior qualifications, low technical familiarity, time constraints, difficulties in recording and systematically analyzing information, as well as reduced participation and engagement. The heterogeneity of sectors and demands also hindered the prioritization of actions, and in some cases, the rigidity of steps compromised adaptation to real work routines. The main improvements suggested involved strengthening training and continuous awareness, standardizing procedures with clear language, simplifying complex steps, expanding intersectoral communication, establishing permanent spaces for participation and the exchange of experiences, and implementing routines for monitoring the actions implemented. These improvement proposals strengthen the institutional capacity to integrate the analysis and transformation of work into the organizational daily routine. From this perspective, the adapted method has the potential to consolidate systematic ergonomic practices, aligned with the real needs of workers and organizational and legal requirements.
Proposal for adapting a method for analyzing work in a higher education institution in Mato Grosso.
Keywords: Análise de Conteúdo; Ergonomia; Organização do Trabalho; Saúde do Trabalhador; Universidade Pública.; Content Analysis; Ergonomics; Work Organization; Worker Health; Public University.; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 3. Saúde e Bem-Estar